A study on the relationship between college students’ creativity and their ability to interpret emojis emotionally - Lee, Seung Min (Edelweiss Applied Science and Technology, 2025)
This study was conducted to evaluate how accurately emoji users can identify the emotions conveyed by emojis in non-face-to-face communication and to inform future directions in emoji design. Specifically, the study aims to explore the relationship between individuals' creative personality traits—defined as the cognitive ability to generate new and appropriate ideas or outcomes—and their capacity to interpret the emotions expressed by emojis. The focus of this research is on university students in their 20s, examining how accurately they recognize the emotions conveyed by emojis and empirically analyzing the relationship between this ability and their creativity. For the study, an online survey was conducted on students from a university in Chungnam, Korea. The results indicate that among the six emotions represented by the emojis used in the study, the emoji depicting happiness had the highest correct response rate, while the emoji representing fear had the lowest. Furthermore, there was no significant difference in the ability to interpret emoji emotions between male and female participants. However, individual creativity was found to influence the capacity to interpret these emotions. The research findings have significant implications for the use of emojis in online conversations with partners from diverse backgrounds.